1995
DOI: 10.1136/gut.36.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal gastric pH in chronic pancreatitis.

Abstract: The aim of this study was to assess the circadian variations of intragastric pH in 28 inpatients with chronic pancreatitis (mean (SD) age 46.8 (12.4) years) and in 14 controls (45.4 (9.8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…120 Gastric acidity also appears to be associated with pancreatic exocrine function: Bovo et al observed an earlier drop in intragastric pH postprandially in patients with decompensated compared with compensated pancreatic exocrine insufficiency. 155 Moreover, there was a positive correlation between median postprandial pH and lipase output. If gastric contents were not aspirated completely, this may not only be explained by the association between the degree of pancreatic exocrine insufficiency and the drop of intragastric pH but also by acidic destruction of lipase intraduodenally.…”
Section: Bicarbonate Output and Duodenal Phmentioning
confidence: 93%
“…120 Gastric acidity also appears to be associated with pancreatic exocrine function: Bovo et al observed an earlier drop in intragastric pH postprandially in patients with decompensated compared with compensated pancreatic exocrine insufficiency. 155 Moreover, there was a positive correlation between median postprandial pH and lipase output. If gastric contents were not aspirated completely, this may not only be explained by the association between the degree of pancreatic exocrine insufficiency and the drop of intragastric pH but also by acidic destruction of lipase intraduodenally.…”
Section: Bicarbonate Output and Duodenal Phmentioning
confidence: 93%
“…5 , 6 In recent studies the concept of an increased acid load to the duodenum was proposed as a factor in addition to impaired pancreatic bicarbonate secretion, resulting in lower duodenal pH in patients with chronic pancreatitis 4 , . 7 –11 Several studies on gastric acid secretion in chronic pancreatitis patients have been performed 3 , 4 , 7 –15 but the results seem to conflict. Interpretation of these data is hampered by differences in methodology, patient selection, ongoing alcohol consumption, and influence of medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Certain investigators have pointed to an increased acid load from the stomach to the duodenum causing the lower intraduodenal pH 4 , . 7 –11 Increased basal and meal or pentagastrin stimulated gastric acid secretion has been observed in chronic pancreatitis patients in some studies 4 , 7 –11 but others failed to demonstrate significant differences in gastric acid secretion between patients with chronic pancreatitis and control subjects 3 , . 12 –15 In some studies gastric acid secretion in chronic pancreatitis patients was even found to be significantly reduced 3 , .…”
Section: Introductionmentioning
confidence: 99%
“…In patients with exocrine pancreatic insufficiency, not only the secretion of pancreatic enzymes, but also secretin-induced secretion of bicarbonate by ductal epithelial cells, as well as the negative feedback mechanism for gastric acid production, are impaired [40, 41]. Furthermore, acid neutralization can be reduced and delayed in the small intestine.…”
Section: Acid Suppressionmentioning
confidence: 99%
“…As a result, the duodenal pH may fall below 4. This leads to a delayed activation of lipase with less activity in the proximal small intestine, causing suboptimal utilization of enzyme activity and resorption capacity [40, 42, 43]. Additionally, bile acid precipitation may affect the enterohepatic cycling of bile [44].…”
Section: Acid Suppressionmentioning
confidence: 99%